HUBUNGAN KECERDASAN SPIRITUAL TERHADAP SIKAP BELAJAR SISWA PADA PEMBELAJARAN PAI DI SMK NEGERI 1 BEKASI - Suharyat, Yayat (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
The study aims to find out the relation of the student's spiritual intelligence to the attitude of learning education in Islam. The learning of Islamic religious education can be said to be successful when learners are able to master the material and use its learning to apply to everyday life. Success in learning learners can be measured by assessments of results. A low learning attitude is characterized by many students who still want to play, distracting students who are learning focus, not enthusiastic, not serious about attending study activities, sometimes getting sleepy in class and not sure of the importance of learning. This suggests that students are less motivated in learning about Islamic education. The study uses quantitative research, this research is conducted to explain, test links between variables, and determine kasalities of variables, test theories and search for predictive value generalities. A sample of this study is citizen SMK city of bekasi. The study uses a data collection of literature and questionnaires. The spiritual intelligence of learners is also implemented into everyday life, it is in the can from the indicator of spiritual intelligence 'I am patient and do not complain when going through trials' there are 53.3% highly approved learners, 36.7% approved, 6.7% disagreeable and 3.3% trainees strongly disagree, And the attitude indicators for learning the 'islamic religious education education need to be studied because it benefits world and afterlife' are 73.3% of the students who strongly agree with this.